Experimental investigation of vibrations and noise characterization for spark ignition engine - Erdiwansyah, .; M. S. M., Sani; R., Mamat; J. M., Zikri; N. F. D., Razak; Munawir, . (IOP Publishing, 2019)
An experimental study was carried out for measuring vibrations, noise and combustion characteristics associated correlations using a four-cylinder spark ignition engine. This study aims to investigate the effects of vibrations and noise on spark-polishing machines that are triggered by pure gasoline. This test runs at 15% engine load and 20% with engine speed 1000-2200 rpm at intervals of 300 rpm. The measurement of engine vibration in pistonic uses PCB Piezotronics ICP® Accelerometer (352C22). Overall tests that have been carried out for 20% loads at 1900 and 2200 maximum vibrations, the velocity is 0.214 and 0.234, compared to 0.617 and 0.562 for 15% loads. From the results of engine vibration analysis, it can be reported that increasing engine speed and the load is given engine vibration can significantly decrease. Generally, noise increases for all samples tested; however, reduced noise is recorded when speed and engine load increase. This observation is also consistent with other observations related to vibration and combustion noise, heat release rates, and ignition delays.